2019
DOI: 10.1109/jbhi.2019.2918687
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of e-Social Activity in Psychiatric Patients

Abstract: This work introduces a novel method to assess the social activity maintained by psychiatric patients using information and communication technologies. In particular, we model the daily usage patterns of phone calls and social and communication apps using point processes. We propose a novel nonhomogeneous Poisson process model with periodic (circadian) intensity function using a truncated Fourier series expansion, which is inferred using a trust-region algorithm. We also extend the model using a mixture of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Data were drawn from two ongoing studies with psychiatric outpatients in Madrid, Spain that involve remote smartphone monitoring [ 24 , 25 ]. Both studies received ethical approval from the Fundación Jimenez Diaz Hospital Institutional Review Board, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from two ongoing studies with psychiatric outpatients in Madrid, Spain that involve remote smartphone monitoring [ 24 , 25 ]. Both studies received ethical approval from the Fundación Jimenez Diaz Hospital Institutional Review Board, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies that design machine learning models to classify and predict mental states use metrics such as accuracy, precision, recall, whereas in our unsupervised sociability pattern learning approach, we use methods to assess the ability to model social routine and detect behavior changes. The works [22][23][24] also assess sociability patterns, but they differ from our experiments. Harari et al [23] computed test-retest correlations between the observed behavior durations for adjacent weeks.…”
Section: Discussion and Limitationsmentioning
confidence: 76%
“…For example, some studies develop machine learning models to classify and predict mental states, while our solution aims to extract sociability patterns and detect behavior changes. The works [22][23][24] also propose solutions capable of detecting sociability patterns, but they differ from our solution. These works design sociability patterns to quantify the duration and frequency of social interactions, while our solution recognizes periods of the day representing individuals' social routine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations